Valproic Acid Enhances Venetoclax Efficacy in Targeting Acute Myeloid Leukemia - Renshi Kawakatsu; Kenjiro Tadagaki; Kenta Yamasaki; Yasumichi Kuwahara; Tatsushi Yoshida (Diseases)
Background: Acute myeloid leukemia (AML) is a common and aggressive form of leukemia, yet current treatment strategies remain insufficient. Venetoclax, a BH3-mimetic approved for AML treatment, induces Bcl-2-dependent apoptosis, though its therapeutic efficacy is still limited. Therefore, new strategies to enhance the effect of venetoclax are highly sought. Valproic acid (VPA), commonly used for epilepsy, has also been studied for potential applications in AML treatment. Methods: AML cells were treated with venetoclax, with or without VPA. Cell viability was assessed using the trypan blue dye exclusion assay, while cell cycle progression was analyzed by flow cytometry. The expression of pro-apoptotic proteins Bax and Bak was measured by RT-qPCR. Results: Venetoclax and VPA individually had only mild effects on AML cell proliferation. However, their combination significantly inhibited cell growth and triggered pronounced cell death. This combination also led to the cleavage of poly (ADP-ribose) polymerase (PARP), a substrate of caspases, indicating activation of apoptosis. VPA treatment upregulated the expression of Bax and Bak, further supporting apoptosis induction. The cell death induced by the venetoclax–VPA combination was predominantly apoptotic, as confirmed by the near-complete blockade of cell death by a pan-caspase inhibitor. Conclusions: Our study demonstrates that VPA enhances venetoclax-induced apoptosis in AML cell lines, providing a novel role for VPA and suggesting a promising combinatory strategy for AML treatment. These findings offer valuable insights into potential clinical applications of venetoclax and VPA in AML management.